Evaluation of antimicrobial activity of extracts and fractions of species of the genus psychotria - de Freitas Junior, Adilso; Ribeiro de Carvalho Junior, Almir; de Fraga, Fernando Bueno Ferreira Fonseca; Nandi, Ana Júlia Ricardo; Vieira, Ivo José Curcino; da Silva, Paulo Sérgio; Braz-Filho, Raimundo (Seven Editora, 2023)
Alkaloids are secondary metabolites, present in plants, which have been exhibiting a series of biological activities, a fact that highlights the importance of research with this theme. The work developed from August/2019 to August/2020, in the laboratories of the IFSC - Campus Criciúma, aimed to isolate, purify and evaluate antimicrobial activities of extracts, fractions and substances isolated from species of Psychotria genus.The extracts were obtained by maceration of the species leaves in methanol. The fractions were obtained by liquid-liquid extraction and the isolation processes by chromatographic methods. The identification of the tested metabolite was performed by NMR of1 H,13 C and high resolution mass spectrometry.The antimicrobial tests were made with the alkaloid 5-carboxy-strictosidine, extracted from Psychotria nuda, against the following microorganisms: Escherichia coli, Staphylococcus epidermidis and Pseudomonas aeruginosa. Sample did not show any activity when compared to the positive control.DOI: https://doi.org/10.56238/colleinternhealthscienv1-033